Real-Time Feedback Signal Processing: Transforming Customer Surveys into Actionable Intelligence Through NLP-Driven Architectures - Chebrolu, Madhusudhanarao (International Journal of Computing and Engineering, 2025)
Traditional survey mechanisms fail to meet the speed and scale requirements of modern customer-centric organizations, creating critical gaps between customer expression and business response. This work presents a comprehensive real-time feedback loop architecture that transforms passive survey data into intelligent, actionable signals through integrated NLP-based analysis, structured moderation logic, and automated decision routing. The proposed system leverages streaming data ingestion pipelines, multi-tier sentiment and intent classification models, and domain-specific moderation engines to enable programmatic routing of customer feedback to relevant business functions. Implementation across e-commerce, SaaS, and AdTech platforms demonstrates significant reductions in support resolution times, improved escalation efficiency, and enhanced customer satisfaction metrics. The architecture incorporates open-source NLP engines, background job processors, consent-aware data pipelines, and contextual prioritization models, providing a scalable and privacy-conscious solution. By eliminating the latency inherent in batch-processed feedback systems, organizations can detect dissatisfaction signals immediately, route issues dynamically based on severity and sentiment, and generate predictive insights for proactive intervention. The framework's modular design enables flexible integration with existing customer relationship management systems while maintaining high throughput and classification accuracy across diverse feedback channels